Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pasien UPTD Puskesmas Cipedes Tasikmalaya : Survei pada Pasien UPTD Puskesmas Cipedes Kota Tasikmalaya - Destia Nur Wiardi; Ari Arisman; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of service quality and facilities on satisfaction (Survey of Patient UPTD Puskesmas Cipedes in Tasikmalaya City) The method used is quantitative with causality method and survey approach. With a research sample of 100 consumers of UPTD Puskesmas Cipedes in Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The result showed that simultaneously the quality of service and facilities had a significant effect on patient satisfaction. Partially, service quality has a significant effect on patient satisfaction, while facilities have no significant effect on patient satisfaction.